Hukum Islam dalam Pembentukan Keluarga Sakinah Mawaddah Warahmah (Field Research di KUA Kalisat Jember) - Afifah, Nurul Afifah; Abdul Halim (Fakultas Syariah Program studi Hukum Keluarga Islam IAI Al- Qodiri, 2024)
A Sakinah family is a family formed based on a legal marriage, able to provide affection to its family members so that they have a sense of security, tranquility, peace and happiness in trying to achieve the welfare of the world hereafter. To realize a sakinah family is not an easy thing. There needs to be efforts that lead to the process. Among other things, the awareness of family members, socialization, guidance and encouragement to them to instill the values of forming a sakinah family. There are still many households that are plagued by conflict so that the impact on the destruction of the family order ranging from children to the environment. The context of this research is How is the concept of a sakinah family mawaddah warahmah from the perspective of Islamic law a study of the views of religious leaders and the head of the kalisat sub-district KUA?. The results of this study reveal the concept of a Sakinah Family Mawaddah Warahmah Perspective of Islamic Law, a study of the views of religious leaders and the head of the KUA of Kalisat District, namely that a sakinah family means tranquility, peace and tranquility.